(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2014)
If we are ever to achieve the goal of redirecting technological development along more environmentally and socially responsible lines we need to provide students with opportunities to examine the processes of science and technology, the possible costs and consequences of this work, and the choices available to us. The purpose of this study is to examine students’ developing environmental literacy in the Heat Game. The Heat Game is a game-like approach to curriculum designed to support students developing their environmental literacy while addressing curriculum requirements for a grade 7 unit, Heat in the Environment, in Ontario, Canada. Based on principles of learning in video-games, the Heat Game recreates a simulation of a science and technology setting wherein student-participants role-play junior professional scientists communicating online within a community of scientists. In their roles they work to solve a virtual challenge to design energy-efficient housing, and reflect on possible environmental and societal consequences of their designs. This study, which is part of a larger design-based research study of The Heat Game, uses discourse analysis to examine online role-playing conversations generated within the game as well as online correspondence between students and their teacher after the game. The study demonstrates that through actions and online conversations in the Heat Game students developed their environmental literacy, including understandings of the relationships between science, technology and the environment and the consequences of choices we make. In addition the study provides support for the ideas of Gee (2007) regarding how we can use the principles of learning in video games to create opportunities for students to develop a literacy; in this case environmental literacy.